Online Learning Evaluation of Moodle-Based Quality Assurance Management on Self-Regulated Learning Capabilities - Himawan Aditya Pratama; Wegig Pratama; Waris Wibowo; Ningrum Astriawati (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The research conducted aims to evaluate Moodle-based online learning in Quality Assurance Management courses from aspects: (1) The ability of cadets to use Moodle; (2) The active communication of cadets and lecturers in the use of Moodle; and (3) Self-Regulated Learning Capabilities in Quality Assurance Management Courses. The research methods to be used use descriptive research. The subject of the study is a cadet who takes quality assurance management courses. Data collection techniques use (1) a questionnaire to obtain information from cadets; (2) Documentation, i.e. retrieving log data on Moodle; and (3) Interviews, to obtain data from lecturers related to ability and activity, Interviews in this study use unstructured interviews. The results showed that: (1) Cadets can follow the learning process using Moodle-based online learning, (2) The activeness of communication of cadets and lecturers in the use of Moodle falls into the good category, and (3) Self-Regulated Learning Skills in Quality Assurance Management Courses fall into the good category.